Tax-motivated transfer mispricing in South Africa: Direct evidence using transaction data - Ludvig Wier (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper provides the first direct systematic evidence of profit shifting through transfer mispricing in a developing country. Using South African transaction-level customs data, I directly test for transfer price deviations from arm's-length pricing. I find that multinational firms in South Africa manipulate transfer prices in order to shift taxable profits to low-tax countries. The estimated tax loss is 0.5 per cent of corporate tax payments. My estimates do not support the common belief that transfer mispricing in South Africa is more severe than in advanced economies. I find that an OECD-recommended reform had no long-term impact on transfer mispricing but argue that the method used in this paper provides a cost-efficient way to curb transfer mispricing.
Keywords: H25; H26; H87; O23; 330; tax; international taxation; profit shifting; multinational firms; developing countries